Hot shearing processes: Correlation of numerical simulation with real wear phenomena. (February 2015) - Torres, H.; Horwatitsch, D.; Varga, M.; Schuster, M.; Adam, K.; Rodríguez Ripoll, M.
Abstract: Metal sheet shearing is a necessary procedure for dimensional control during steel forming. Due to extreme operating conditions, shearing blades suffer from severe wear and need frequent repair, causing high maintenance costs. In order to increase the lifetime of cutting blades, FEM simulation of the metal shearing process was performed, implementing a hybrid friction coefficient based on data obtained from a newly developed forming tribometer. A good correlation was found between the shape of the sheared work piece as predicted by the FEM model and as found in the real application. Finally, a relationship is proposed between stress and temperature distributions as calculated by the simulation and shearing blade areas most affected by wear. Highlights: FE simulation of hot shearing was performed, using a hybrid friction model. The simulation accurately modelled the profile of sheared work piece. Cutting blade tensile stress was correlated with an observed wear track. A predicted shear stress peak correlated with flank face plastic deformation. Temperature-induced shear stress at the cutting edge was linked to thermal fatigue.